Mutational analysis of the helper component-proteinase gene of a potyvirus: effects of amino acid substitutions, deletions, and gene replacement on virulence and aphid transmissibility. - Atreya, C D (1993)
We have previously provided evidence that amino acid substitutions within the N-terminal portion of the helper component-proteinase (HC-Pro) from tobacco vein mottling virus (TVMV), in particular at Lys-307, not only affect the aphid transmission activity of HC-Pro but also have a significant effect on TVMV virulence. In the present study amino acids which differ in their charge properties were substituted at position 307. A highly basic residue was required to retain helper component activity and virulence. Deletion and insertion mutagenesis in the 5' terminus of the HC-Pro gene suggested that this RNA domain may be an essential element for TVMV infectivity. Replacement of the TVMV HC-Pro gene with that from another potyvirus, zucchini yellow mosaic virus, maintained infectivity and aphid transmissibility of the chimeric virus, although symptoms were attenuated. Our results suggest that, in addition to its importance in aphid transmission, the HC-Pro gene may be of general importance in regulating virulence of potyviruses, possibly by interaction of these sequences with the host.